Exploring the Proximate, Phytochemical, and Antioxidant Potential of Hemp and Parthenium Residues - Muhammad Usman; Afia Zia; Muhammad Nauman Ahmad; Sahib Alam; Tariq Aziz; Majid Alhomrani; Walaa F Alsanie; Abdulhakeem S Alamri (BioResources, 2025)
Improper disposal of agricultural residues is becoming a looming environmental issue as a major contributor to pollution and depletion of natural resources. The current study aimed to evaluate the proximate compositions, phytochemical profile along with antioxidant properties of the residues of hemp (Cannabis sativa) and parthenium (Parthenium hysterophorus) as sustainable resources. The standard protocol of AOAC was followed for proximate analysis. Phytochemical profiling was done to identify key bioactive compounds through qualitative assays. Their antioxidant activity was assayed by DPPH (2,2-diphenyl-1-picrylhydrazyl) free radical scavenging. Hemp recorded 50.2% more fibers than parthenium at 27.5% making it a better candidate for bio-material development. Future in vivo studies are recommended to elucidate the metabolic effects of these plants and their potential health benefits. Phytochemical analysis revealed the presence alkaloids, flavonoids, tannins, steroids, coumarins, and sterols, thus showing their bioactivity and possible health benefits. The antioxidant activity was significantly increased in hemp residues (0.1 ± 0.13 mg Trolox/g) compared to parthenium (0.057 ± 0.21 mg Trolox/g), whereas the activity from aerial parts was found lower. This demonstrates the wider application potentials of these residues in the industrial and pharmaceutical sectors as eco-friendly substitutes for conventional materials.